2000
DOI: 10.1002/1521-3765(20000602)6:11<1947::aid-chem1947>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Cyclophane: Design, Synthesis, and Structure of a Multibridged Tris-tetrathiafulvalene (TTF) Macrocycle

Abstract: The tris-tetrathiafulvalene (TTF) macrocycles 3 with a large end-cavity were effectively synthesized from the readily available tetrakis(cyanoethylthio)TTF by means of a selective deprotection/realkylation sequence followed by an intramolecular coupling reaction. Crystar structure analyses revealed that the neutral molecules include two (3a) or one chloroform molecule (3b) as solvent of crystallization inside the cavity, whereas the I3- salt of 3b, obtained by electrocrystallization, has a molecular structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A comparison of the structure of the neutral TTF cage molecule 65 with the structure of the oxidized 65 + showed that the two forms adopt completely different molecule shapes. The neutral end cavity that encapsulated one CHCl 3 molecule in the neutral 65 collapses completely upon oxidation as depicted in Figure , and the oxidized molecule 65 + folds to effectively minimize the volume of cavity . These observations clearly illustrate that intramolecular interactions between the cationic and neutral TTF units are taking place and play an important role in the stabilization of the collapsed molecular shape of 65 + .…”
Section: 2 Ttf Cage Moleculesmentioning
confidence: 82%
See 2 more Smart Citations
“…A comparison of the structure of the neutral TTF cage molecule 65 with the structure of the oxidized 65 + showed that the two forms adopt completely different molecule shapes. The neutral end cavity that encapsulated one CHCl 3 molecule in the neutral 65 collapses completely upon oxidation as depicted in Figure , and the oxidized molecule 65 + folds to effectively minimize the volume of cavity . These observations clearly illustrate that intramolecular interactions between the cationic and neutral TTF units are taking place and play an important role in the stabilization of the collapsed molecular shape of 65 + .…”
Section: 2 Ttf Cage Moleculesmentioning
confidence: 82%
“…Hydrogen atoms are omitted for clarity. (Reprinted with permission from ref . Copyright 2000 Wiley-VCH.)…”
Section: 2 Ttf Cage Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a criss-cross tris-TTF cyclophane with C 1 symmetry has been reported. 9 The crystal structures of this neutral donor molecule and cation radical salt of the I 3 2 counter anion showed redox active conformational change. 9 We employed here the tris(DMT-TTF) having C 3 molecular symmetry as a TTF trisannulated macrocycle (Chart 1).…”
Section: Introductionmentioning
confidence: 94%
“…9 The crystal structures of this neutral donor molecule and cation radical salt of the I 3 2 counter anion showed redox active conformational change. 9 We employed here the tris(DMT-TTF) having C 3 molecular symmetry as a TTF trisannulated macrocycle (Chart 1). 7a The linkers between three DMT-TTF units are propyldithio groups, ±S±(CH 2 ) 3 ±S±.…”
Section: Introductionmentioning
confidence: 94%